History of the College for the Deaf, 1857-1907 - Gallaudet, Edward Miner, 1837-1917; Fischer, Lance J., 1949-; De Lorenzo, David L., 1952-; Merrill, Edward C. (Washington, D.C. : Gallaudet College Press, 1983)
Index
Includes index.
Keywords: Gallaudet College -- History -- 19th century